KONTRIBUSI DANA BOS TERHADAP SISWA MISKIN DI LIMA SEKOLAH SWASTA DI KECAMATAN CAKUNG JAKARTA TIMUR - Sa'diyah El Adawiyah (El-Idare, 2016)
The high Budget allocation in the education sector it is still not helping to improve access and quality of education. Currently in Indonesia there are about 465 500 children aged 7-12 years who have not entered elementary school, and 1.2 million children aged 13-15 who are not in junior high school. The dropout rate in elementary schools reached 13 percent. Objective: 1) Knowing the contribution of BOS funds to poor students in private schools in East Jakarta. 2) Determine the accuracy of the allocation of BOS funds for poor students in private schools in East Jakarta. 3) Knowing the role of parents in the implementation of the BOS program at the private school in East Jakarta. The study uses quantitative methods in five poor school swassta Cakung, East Jakarta.